Community prevalence and distribution of dengue virus serotype based on antibody neutralization assay in Jakarta, Indonesia - Karyanti, Mulya Rahma; Alam, Anggraini; Widyahening, Indah Suci; Hadinegoro, Sri Rezeki; Munasir, Zakiudin; Satari, Hindra Irawan; Sasmono, R. Tedjo (Indonesian Pediatric Society, 2025)
Background Dengue infection is still rising globally despite the implementation of preventive efforts in many endemic countries. Monitoring the circulation of dengue virus (DENV) serotypes is not performed routinely in the Indonesian national surveillance program, primarily due to high cost and effort. Objective To evaluate the distribution of DENV serotypes based on serological profile and neutralizing antibody level against all four DENV serotypes in Jakarta, Indonesia. Methods This cross-sectional study was performed as part of a dengue vaccine effectiveness study, 10 years after a dengue vaccination program was initiated. It was conducted in five community public health centers in Jakarta in subjects aged 12 years and above who had not received the dengue vaccine. We collected serum samples and DENV neutralizing antibody titers were measured using a plaque reduction neutralization test (PRNT). Results Eighty healthy subjects with a median age of 15 (range 12-27) years were enrolled. The highest median antibody titer was that to DENV-2 [898 (range 29-91558) 1/dil], followed by that to DENV-3 [297.5 (range 10-36091); 1/dil], DENV-1 [288 (range 0-68237) 1/dil], and DENV-4 [164 (range 0-35812) 1/dil]. Neutralizing antibodies against the four DENV serotypes were found in all the 5 districts studied in Jakarta. A multitypic neutralizing antibody profile was observed in the majority (74/80 subjects; 92.5%). Three subjects were naïve. Conclusion All four dengue serotypes are widely circulating in Jakarta based on neutralizing antibody detection in the community, with the highest neutralizing antibody titer being against DENV-2, followed by DENV-3, DENV-1 and DENV-4.